Multi-allelic gene editing in an apomictic, tetraploid turf and forage grass (Paspalum notatum Flüggé) using CRISPR/Cas9 - May, David; Sanchez, Sara; Gilby, Jennifer; Altpeter, Fredy (Frontiers in Plant Science, 2023)
Polyploidy is common among grasses (Poaceae) and poses challenges for conventional breeding. Genome editing technology circumvents crossing and selfing, enabling targeted modifications to multiple gene copies in a single generation while maintaining the heterozygous context of many polyploid genomes. Bahiagrass (Paspalum notatum Flüggé; 2n=4x=40) is an apomictic, tetraploid C4 species that is widely grown in the southeastern United States as forage in beef cattle production and utility turf. The chlorophyll biosynthesis gene magnesium chelatase (MgCh) was selected as a rapid readout target for establishing genome editing in tetraploid bahiagrass. Vectors containing sgRNAs, Cas9 and nptII were delivered to callus cultures by biolistics. Edited plants were characterized through PCR-based assays and DNA sequencing, and mutagenesis frequencies as high as 99% of Illumina reads were observed. Sequencing of wild type (WT) bahiagrass revealed a high level of sequence variation in MgCh likely due to the presence of at least two copies with possibly eight different alleles, including pseudogenes. MgCh mutants exhibited visible chlorophyll depletion with up to 82% reductions in leaf greenness. Two lines displayed progression of editing over time which was linked to somatic editing. Apomictic progeny of a chimeric MgCh editing event were obtained and allowed identification of uniformly edited progeny plants among a range of chlorophyll depletion phenotypes. Sanger sequencing of a highly edited mutant revealed elevated frequency of a WT allele, probably due to frequent homology-directed repair (HDR). To our knowledge these experiments comprise the first report of genome editing applied in perennial, warm-season turf or forage grasses. This technology will accelerate bahiagrass cultivar development.